Hubungan antara Diameter Optic Nerve Sheath pada Grey Scale Ultrasound dengan Peningkatan Tekanan Intrakranial pada Pasien dengan Lesi Intrakranial - Tatok Rudiharto; Bachtiar Murtala; Sri Asriyani; Mirna Muis; Cahyono Kaelan; Burhanuddin Bahar (Lembaga Penelitian Universitas YARSI, 2019)
The study aims to determine the correlation between diameter of optic nerve sheath on grey scale with increased intracranial pressure in patients with intracranial lesion. The research was conducted in Radiology Department of Dr. Wahidin Sudirohusodo Makassar from January 2019 – May 2019. The sample were 39 people aged ³18 years old with intracranial lesion. Axial computed tomography (CT) examination was performed to evaluate intracranial lesions and the presence of midline shift. The diameter of the optic nerve sheath was measured using eye ultrasonography. Data analyses used Spearman’s correlation test. The results showed that there was a correlation between the dilatation of the right and left optic nerve sheath diameter with midline shift (p value 0.04; p less than 0.05) on the diameter of the right optic nerve sheath showing a weak positive relationship (p value 0.02) for the diameter the optic nerve sheath left showing a medium positive relationship where the higher the midline shift, the wider the diameter of the left and right optical nerve sheath. There is a correlation between the right and left optic nerve sheath diameter (p less than equal 0.001) showing a strong positive relationship where the wider the diameter of the right optic nerve sheath, the wider the diameter of the left optic nerve sheath at high intracranial pressure. Statistically other results also obtained no relationship between dilatation of the diameter of the optic nerve sheath with clinical symptoms of increased intracranial pressure and type of lesion.